Electrolytic solution for electrochemical corrosion control method, and electrochemical corrosion control method
The use of a lithium-ion-based electrolyte solution with specific ion ratios in electrochemical treatments addresses the challenges of salt damage and ASR in reinforced concrete, achieving effective corrosion prevention and enhanced durability.
Patent Information
- Application Number
- JP2023163018
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-07
AI Technical Summary
Existing electrochemical treatment methods for reinforced concrete do not adequately address salt damage and Alkaline Aggregate Reaction (ASR), leading to corrosion and reduced durability of concrete structures.
An electrolyte solution containing 1.0 to 8.0 mol/L of lithium ions, with nitrate ions and/or carbonate ions, and specific concentration ratios, is used to enhance corrosion prevention and ASR expansion suppression in electrochemical treatments.
The electrolyte solution effectively prevents corrosion of reinforced bars and inhibits ASR expansion, significantly improving the durability of concrete structures by maintaining a low concrete expansion rate and high pH levels.
Smart Images

Figure 2025053903000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolyte for an electrochemical corrosion prevention method and an electrochemical corrosion prevention method. [Background technology]
[0002] Traditionally, reinforced concrete has generally been used for the construction of civil engineering structures such as roads and railways, specifically bridge substructures, bridge girders, underground structures such as tunnels, semi-underground structures, culverts, etc. This reinforced concrete is widely used as a structural material because it is possible to create a composite structure that has both compressive strength and tensile strength by combining concrete, which has high compressive strength performance, with reinforcing bars, which have high tensile strength performance. Structures that use this reinforced concrete are known as PC structures, and there are many concrete structures in which PC steel materials (PC steel wires, PC steel bars, PC steel strands, etc.) are placed within the concrete.
[0003] Concrete has high environmental resistance, and the concrete itself is strongly alkaline with a pH of 12 to 12.5. Therefore, it was thought that reinforcing bars placed inside the concrete would form a passive film on their surface, protecting them from corrosion.
[0004] However, in recent years, deterioration of reinforced concrete structures due to salt damage and alkali-aggregate reaction (ASR) has become a social problem. Here, "salt damage" refers to a deterioration phenomenon in which, in the case of concrete structures in coastal areas, when seawater splashes onto the surface of the concrete, the salt penetrates the concrete due to the adsorption phenomenon of the concrete and the concentration gradient, reaching the reinforcing bars, where the chloride ions destroy the passive film of the reinforcing bars, initiating corrosion. Furthermore, in past concrete structures, sea sand was sometimes used as fine aggregate, and if it was used without sufficient salt removal, a large amount of chloride would be present in the concrete, which resulted in the destruction of the passive film of the reinforcing bars and the initiation of corrosion in some cases. In addition, "alkali aggregate reaction (ASR)" is a deterioration phenomenon in which alkali silica gel formed by a chemical reaction between alkali metals in concrete and substances contained in the aggregate expands due to moisture that penetrates into the concrete, causing cracks. As the above-mentioned deterioration phenomenon of reinforced concrete progresses, the durability of the composite structure will be significantly reduced.
[0005] As a method for treating deteriorated reinforced concrete, in addition to methods that involve destruction of the structure, such as chipping off the deteriorated parts and backfilling them with concrete or mortar, non-destructive treatment methods using electrochemical methods have been proposed and implemented.
[0006] For example, Patent Document 1 proposes a method for electrochemical treatment of reinforced concrete, in which an external electrode is disposed on one side of a plate-like body, a large number of electrode unit panels are prepared in which the entire area where the external electrodes are disposed is covered with an electrolyte solution retention material made of a fibrous sheet, the electrode unit panels are arranged side by side on the concrete surface to be treated, and liquid-tightness is ensured in the joints and outer periphery between adjacent electrode unit panels, an electrolyte solution supply port is provided at any desired location, and an electrolyte solution recovery port is provided, and electrolyte solution is continuously or intermittently supplied between the electrode unit panel and the concrete surface from the electrolyte solution supply port and the electrolyte solution is recovered from the electrolyte solution recovery port. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 6586000 Summary of the Invention [Problem to be solved by the invention]
[0008] The electrochemical treatment method for reinforced concrete described in Patent Document 1 is expected to have various benefits, such as eliminating the need to spray cellulose fiber and electrolyte solution, maintaining a good working environment, and ensuring the safety of workers. It is also possible to minimize the generation of special industrial waste, reduce the amount of electrolyte solution used, and reduce the labor required for water supply work.
[0009] However, there are many unclear points regarding the mechanism by which the above-mentioned salt damage and ASR occur in combination and cause deterioration, and efficient construction methods that take both into consideration are being sought. In particular, in the electrochemical treatment methods mentioned above, electrolytes have not yet been fully examined.
[0010] In view of the above, an object of the present invention is to provide an electrolyte for use in an electrochemical corrosion protection method that exhibits excellent effects of preventing corrosion of reinforcing bars and suppressing ASR expansion. [Means for solving the problem]
[0011] As a result of intensive research conducted by the present inventors in light of the above problems, they found that an electrolyte for electrochemical corrosion protection containing 1.0 to 8.0 mol / L of lithium ions can solve the above problems, and thus completed the present invention. That is, the present invention is as follows.
[0012] [1] An electrolyte for electrochemical corrosion protection containing 1.0 to 8.0 mol / L of lithium ions. [2] The electrolyte for electrochemical corrosion protection according to the above [1], which contains nitrate ions and / or carbonate ions. [3] The electrolyte for electrochemical corrosion protection according to the above [2], wherein the ratio of the concentration of the lithium ions to the concentration of the nitrate ions (Li / NO3) is 1.0 to 3.0. [4] The electrolyte for electrochemical corrosion protection according to the above [2], wherein a ratio of the concentration of the lithium ions to the concentration of the carbonate ions (Li / CO3) is 8 to 60. [5] The electrolyte for electrochemical corrosion protection according to any one of the above [1] to [4], which has a pH of 7 or more. [6] Electrolyte temperature 40℃ and current density 2.0A / m 2 Or electrolyte temperature 30℃ and current density 1.5A / m 2 The electrolyte for electrochemical corrosion protection according to any one of the above [1] to [5], wherein the expansion rate of concrete after performing an electrochemical corrosion protection method under the above current flow conditions for 8 weeks is 0.1% or less. [7] An electrochemical corrosion protection method for concrete, comprising using the electrolyte for electrochemical corrosion protection method according to any one of [1] to [6] above. [8] Electrolyte temperature 40℃ and current density 2.0A / m 2 Or electrolyte temperature 30℃ and current density 1.5A / m 2 The electrochemical corrosion protection method for concrete according to the above-mentioned [7], wherein the pH of the electrolyte after applying an electric current for 8 weeks under the above-mentioned electric current conditions is 7 or more. Effect of the Invention
[0013] According to the present invention, it is possible to provide an electrolyte for an electrochemical corrosion protection method that exhibits excellent effects of preventing corrosion of reinforcing bars and suppressing ASR expansion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present invention (the present embodiment) will be described in detail, but the present invention is not limited to the embodiment. In addition, "%" in this specification is based on mass unless otherwise specified.
[0015] [Electrolyte for electrochemical corrosion protection] The electrolyte for electrochemical corrosion protection according to this embodiment contains lithium ions at 1.0 to 8.0 mol / L. By containing lithium ions at 1.0 to 8.0 mol / L, the electrolyte for electrochemical corrosion protection according to the present invention exhibits excellent rebar corrosion prevention effects and ASR expansion suppression effects.
[0016] The electrolyte for electrochemical corrosion protection preferably contains 1.1 to 7.0 mol / L of lithium ions, more preferably 1.2 to 6.5 mol / L. The lithium ion concentration within the above range can provide better rebar corrosion protection and ASR expansion suppression effects. In the present invention, the lithium ion concentration can be measured by adding a nitric acid solution until the pH of the electrolyte becomes 5 or less, and then using an atomic absorption spectrometer.
[0017] The electrolytic solution for electrochemical corrosion protection according to the present embodiment preferably contains nitrate ions and / or carbonate ions, more preferably nitrate ions and carbonate ions. By containing nitrate ions and / or carbonate ions, the effect of preventing corrosion of reinforcing bars is more excellent, and the effect of suppressing ASR expansion is more easily achieved.
[0018] When the electrolytic solution for electrochemical corrosion protection according to the present embodiment contains nitrate ions, the ratio of the concentration of lithium ions to the concentration of nitrate ions (Li / NO3) is preferably 1.0 to 3.0, more preferably 1.1 to 2.0, and even more preferably 1.2 to 1.5. When the molar concentration ratio Li / NO3 is within the above range, the effect of preventing corrosion of reinforcing bars is more excellent, and the effect of suppressing ASR expansion is more easily achieved. In the present invention, the concentration of nitrate ions can be measured by diluting the electrolytic solution with pure water and subjecting the solution to ion chromatography.
[0019] When the electrolytic solution for electrochemical corrosion protection according to the present embodiment contains carbonate ions, the ratio of the lithium ion concentration to the carbonate ion concentration (Li / CO3) is preferably 8 to 60, more preferably 10 to 58, and even more preferably 12 to 55. When the molar concentration ratio Li / CO3 is within the above range, the rebar corrosion prevention effect is more excellent and the ASR expansion suppression effect is more easily achieved. In the present invention, the carbonate ion concentration can be measured by adding a nitric acid solution until the pH of the electrolytic solution becomes 5 or less and using a total organic carbon analyzer.
[0020] The electrolyte for electrochemical corrosion protection can be prepared by dissolving a lithium-containing substance as a solute in water as a solvent. Any substance containing lithium can be used as the solute, such as lithium hydroxide, lithium nitrate, lithium carbonate, lithium silicate, etc.
[0021] The electrolyte for electrochemical corrosion protection may contain solutes containing potassium, calcium, etc. in addition to the above-mentioned solutes containing lithium.
[0022] The electrolyte for electrochemical corrosion protection according to this embodiment preferably has a pH of 7 or more, more preferably 8 or more, and even more preferably 9 or more. In the present invention, the pH can be measured using a pH meter.
[0023] The electrolytic solution for electrochemical corrosion protection according to this embodiment has an electrolytic solution temperature of 40° C. and a current density of 2.0 A / m 2 Or electrolyte temperature 30℃ and current density 1.5A / m 2 After applying current for 8 weeks under the above current application conditions, the expansion rate of the concrete is preferably 0.1% or less, more preferably 0.08% or less, and even more preferably 0.05% or less.
[0024] The electrolyte for electrochemical corrosion protection is 40℃ and the current density is 2.0A / m 2 Or electrolyte temperature 30℃ and current density 1.5A / m 2 After applying electricity for 8 weeks under the above conditions, the total alkali concentration (RO) near the reinforcing bars of the concrete is preferably 0.8% or more, more preferably 1.0% or more, and even more preferably 1.2% or more of the total alkali concentration of the entire concrete. By having the total alkali concentration near the reinforcing bars of the concrete within the above range, the hydroxide ion (OH - ) also tends to accumulate, making it easier to obtain anti-corrosion effects on rebar.
[0025] [Electrochemical corrosion prevention method] The electrochemical corrosion protection method according to the present embodiment is an electrochemical corrosion protection method for concrete that uses the electrolyte for electrochemical corrosion protection of the present invention. The electrochemical corrosion protection method of the present invention is a method for electrochemical corrosion protection of concrete that uses the electrolyte for electrochemical corrosion protection of the present invention. - ) can be removed by causing it to migrate to an external electrode (desalinization method), or an alkaline electrolyte solution can be electrically penetrated into the rebar inside the concrete to restore the alkalinity of neutralized concrete (re-alkalinization method). In addition, because corrosion of rebar progresses through an electrochemical reaction, by continuously passing a direct current through the rebar, the corrosion reaction of the rebar can be electrochemically suppressed, thereby improving the durability of the concrete structure (electrochemical protection method). Also, by electrophoresis of the electrolyte ions present in the electrolyte solution to the rebar (cathode) side, and depositing inorganic electrodeposits in the cracks and on the concrete surface, it is possible to seal cracks that have occurred in the concrete and densify the concrete surface (electrochemical deposition method).
[0026] The electrochemical corrosion protection method according to this embodiment uses an electrolyte temperature of 40°C and a current density of 2.0 A / m 2 Or electrolyte temperature 30℃ and current density 1.5A / m 2 After energizing for 8 weeks under the above energizing conditions, the pH of the electrolyte is preferably 7 or higher, more preferably 8 or higher, and even more preferably 9 or higher. EXAMPLES
[0027] The present invention will be described in more detail below using examples and comparative examples. However, the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention.
[0028] [Examples 1 to 7] <Preparation of electrolyte for electrochemical corrosion protection method> The materials used below were mixed with water in the ratios shown in Table 1 to prepare an electrochemical corrosion protection electrolyte. The prepared electrochemical corrosion protection electrolyte was applied to reinforced concrete (dimensions: 100 mm x 100 mm x 300 mm, rebar position: 50 mm from the surface) at a temperature of 40°C and a current density of 2.0 A / m 2 The electrochemical corrosion protection method was carried out for 8 weeks under the above current flow conditions, and after the method was carried out, the surface condition, ion concentration at the rebar position, concrete expansion rate, and electrolyte pH were measured. In addition, the concrete after the electrochemical corrosion protection method was cured for 90 days under conditions of a temperature of 40°C and a humidity of 95% or more, and the concrete expansion rate was measured after curing.
[0029] (Materials used) LiOH: Honjo Chemical Co., Ltd. LiNO3: Honjo Chemical Co., Ltd. Li2CO3: Honjo Chemical Co., Ltd. Li2SiO3: Honjo Chemical Co., Ltd. K2CO3:AGC Corporation. Ca(OH)2: Kanto Chemical Co., Ltd.
[0030] (Measurement of concentration of various ions) The prepared electrolyte was sampled, and nitric acid solution was added until the pH of the electrolyte became 5 or less. The lithium ion concentration was measured using an atomic absorption spectrometer (Shimadzu Corporation: AA-7000) and the carbonate ion concentration was measured using a total organic carbon analyzer (Shimadzu Corporation: TOC-L). In addition, the prepared electrolyte was sampled and diluted with pure water, and the concentration of nitrate ions was measured by ion chromatography (ICS-2100, manufactured by Thermo Scientific).
[0031] (pH Measurement) The pH of the electrolyte solution was measured before and after the application of a current using a pH meter (Horiba, Ltd.: Handy pH Meter D-53, Electrode 9618S-10D).
[0032] (Surface condition) After the current was turned off, the concrete surface was visually inspected. If the concrete paste had dissolved and even a small amount of fine aggregate was visible, it was judged as unacceptable (×); if no fine aggregate was visible, it was judged as acceptable (◯).
[0033] (Ion concentration at rebar position) Chloride ion concentration (Cl - ): After the current was removed, the total chloride ion concentration in the concrete within a 5 mm range from the center of the rebar was measured in accordance with JIS A 1154:2020 "Test method for chloride ions in hardened concrete." Total alkali concentration (RO): 50 mL of 2 mol / L nitric acid solution was added to the concrete within 5 mm of the center of the collected rebar, then boiled for 5 minutes. After cooling, the solution was collected by suction filtration, and the Na - Concentration and K - The concentration of alkali was measured using an atomic absorption spectrometer (Shimadzu Corporation: AA-7000), and the total alkali concentration was measured as R2O = Na2O + 0.658K2O.
[0034] (Expansion rate) For the concrete after passing a current and after curing, the expansion rate of the concrete was measured in accordance with JIS A 1129-2:2010 "Methods for measuring length change in mortar and concrete - Part 2: Contact gauge method" using a contact gauge (Maruto Seisakusho: MSG-D1) at three locations: directly above the rebar and two locations 25 mm from the center of the rebar, and the average value was calculated.
[0035] [Table 1] [Industrial Applicability]
[0036] The electrolyte for electrochemical corrosion protection of the present invention can be suitably used for electrochemical corrosion protection of reinforced concrete used in bridges, tunnels and the like.
Claims
1. An electrolyte for electrochemical corrosion protection containing 1.0 to 8.0 mol / L of lithium ions.
2. 2. The electrolyte for electrochemical corrosion protection according to claim 1, which contains nitrate ions and / or carbonate ions.
3. The ratio of the concentration of the lithium ions to the concentration of the nitrate ions (Li / NO 3 3. The electrolytic solution for electrochemical corrosion protection according to claim 2, wherein the pH is 1.0 to 3.
0.
4. The ratio of the concentration of the lithium ions to the concentration of the carbonate ions (Li / CO 3 3. The electrolytic solution for electrochemical corrosion protection according to claim 2, wherein the molecular weight of the electrolyte is 8 to 60.
5. 3. The electrolyte for electrochemical corrosion protection according to claim 1 or 2, having a pH of 7 or more.
6. Electrolyte temperature 40°C and current density 2.0 A / m 2 Or the electrolyte temperature is 30° C. and the current density is 1.5 A / m 2 3. The electrolyte for electrochemical corrosion protection according to claim 1 or 2, which has a concrete expansion rate of 0.1% or less after electrochemical corrosion protection is carried out for 8 weeks under the current supply conditions.
7. 3. An electrochemical corrosion protection method for concrete, comprising using the electrolyte for electrochemical corrosion protection according to claim 1 or 2.
8. Electrolyte temperature 40°C and current density 2.0 A / m 2 Or the electrolyte temperature is 30° C. and the current density is 1.5 A / m 2 8. The electrochemical corrosion protection method for concrete according to claim 7, wherein the pH of the electrolyte after energizing for 8 weeks under the energizing conditions is 7 or more.
Citation Information
Patent Citations
Electrochemical treatment method for reinforced concrete and electrode unit panel therefor
JP6586000B2